Translating guidelines into practice for the management of atrial fibrillation: results of an European Heart Rhythm Association Survey. Issue 8 (8th June 2018) - Dan, Gheorghe-Andrei; Iliodromitis, Konstantinos; Scherr, Daniel; Marín, Francisco; Lenarczyk, Radoslaw; Estner, Heidi L; Kostkiewicz, Marcin; Dagres, Nikolaos; Lip, Gregory Y H
Abstract: Despite the huge progress made in the both understanding the mechanisms and the management of atrial fibrillation (AF) this arrhythmia still represents an important health and social burden. Atrial fibrillation is increasing in frequency and is a major cause of death, stroke, heart failure, cognitive decline, and hospitalizations. New data have emerged emphasizing the multidisciplinary approach to better management of this common arrhythmia. Despite the availability of AF management guidelines, practice among European centres may differ from the current guideline recommendations. The scope of the current European Heart Rhythm Association (EHRA) survey is to evaluate the extent of the disparities between clinical practice and the 2016 AF European Society of Cardiology (ESC) guidelines. Our survey examined important topics such as screening for AF, initial therapy, rhythm strategy, and stroke and bleeding risk assessment. In general, there was a high adherence to the new ESC AF guidelines among European cardiologists.